An Analysis of Studentsâ Difficulties in Solving Story Based Problems and Its Alternative Solutions - Rachmawati, Tika Karlina (Universitas Muhammadiyah Surakarta, 2016)
This study aims to analyze the studentsâ difficulties of MTs Negeri Surakarta 1 in solving story based problems on the subject of Pythagoras along with its alternative solutions. This is a qualitative descriptive research. This study illustrates the difficulties of students in solving story based problemsof the subject of Pythagoras. Research subjects in this study is composed of three students of class IX with each capable of high, medium and low. The data collection was condducted using the test method and the method of interview. The results of this study indicate that low-ability students have difficulty in determining the direction of wind direction, understand the intent of the language that is understood about the story, the difficulty in making a mathematical model as well as difficulties in the calculation. Difficulties experienced by the studentswith medium capability are determining the drawing of wind direction, understanding the intent of the language that is understood about the story, and making a mathematical model. While the high-ability students have no significant problems in understanding a story about the subject of Pythagoras, they just forgot to add Â± sign in the answers, and the unit of length in the final calculation. However, the unit length was written in the final conclusions.